Raw material sources of knapped stone tools from the excavation of the Early Bronze Age site at Toumba Thessaloniki, Greece - Stamatia Karageorgiou; Aikaterini Kostaki; Michail Vavelidis; Stelios Andreou (Journal of Lithic Studies, 2016)
This study investigates the origin of the lithic findings from the prehistoric site at Toumba, Thessaloniki in Greece, during the Early Bronze Age (EBA). The artefacts from the excavation were studied in order to compare the raw materials utilized for the manufacture of these tools with the geological occurrences of the corresponding materials in the broader region. This research provides evidence for the provenance of these materials and consequently some insight into the socioeconomic system of the settlement. For this reason, samples of siliceous sediments were chosen from regions with similar geological formations, such as Vasilika and Galatista. Apart from macroscopic examination, both archaeological and petrographic, microscopic examination was also applied in order to identify the microstructure and the mineralogical context, and finally geochemical study by ICP-MS analysis and XRF spectrometry for determining the major, trace and rare earth element concentrations. The comparison of these features with the archaeological features reveals that during the Early Bronze Age there was possibly a relation between Toumba inhabitants and the regions of Vasilika and Galatista for the procurement of chert. The petrographic examination of the lithic findings shows whether the tools are manufactured in the settlement or if there is an import of tools from other sites.